P675 The relationship between gender, severity of disease, treatment type, and employment outcome in patients with inflammatory bowel disease in Israel. (25th January 2019) - Naftali, T; Ein Dor Abarbanel, A; Ruhimovich, N; Bar-Gil Shitrit, A; Sklerovsky-Benjaminov, F; Shirin, H; Matalon, S; Ziv Baran, T; Broide, E
Abstract: Background: Since individuals with IBD typically experience symptoms during their prime years of employment, it raises the question about IBD impact on employment status. Most studies concentrated on absenteeism from work with varying results in different populations. However, absenteeism reflects only one dimension of the ability to work and does not expose the problem of inability to hold a full-time job. We aimed to evaluate the influence of IBD on unemployment and working hours in Israel. Secondary aims were to investigate the correlation between working hours and the type of medical treatment and the impact of severity of disease. Methods: Demographic data, employment status, number of weekly working hours and disease parameters. The data were compared with that of the general Israeli population extracted from the website of the Central Bureau of Statistics. Results: 242 IBD patients were interviewed. Patients median age was 37.04(IQR 30.23–44.68) years, 88 (36.4%) were men and 154 (63.6%)women. Diagnosis of CD was established in 167 (69%) patients and UC in 65(26.9%). There was no significant reduction in employment rates or working hours among the IBD patients comparing to the general population. Immunosuppressive or biologic treatment did not influence employment status. The unemployed patients had higher disease severity (median 7.33, IQR 5–10.66) compared with employed patients (median 6, IQR 3.66–7.66; p = 0.003). Conclusions: Although IBD patients in Israel do not have higher unemployment, those with severe disease have lower proportion of employment.